Internal replacement of a vertebral body in pseudarthrosis—Armed kyphoplasty with bone graft-filled stents: Case report - Moura, Diogo Lino; Cavaca, Ana Rita (Frontiers in Surgery, 2023)
Background: Post-traumatic vertebral necrosis and pseudarthrosis represents one of the most concerning and unpredictable challenges in spinal traumatology. The evolution of this disease at the thoracolumbar transition usually courses with progressive bone resorption and necrosis, leading to vertebral collapse, retropulsion of the posterior wall and neurological injury. As such, the therapeutic goal is the interruption of this cascade, seeking to stabilize the vertebral body and avoid the negative consequences of its collapse. Case description: We present a clinical case of a pseudarthrosis of T12 vertebral body with severe posterior wall collapse, treated with removal of intravertebral pseudarthrosis focus by transpedicular access, T12 armed kyphoplasty with VBS® stents filled with cancellous bone autograft, laminectomy and stabilization with T10-T11-L1-L2 pedicle screws. We present clinical and imaging detailed results at 2-year follow-up and discuss our option for this biological minimally invasive treatment for vertebral pseudarthrosis that mimics the general principles of atrophic pseudarthrosis therapeutic and allows to perform an internal replacement of the necrotic vertebral body, avoiding the aggression of a total corpectomy. Conclusions: This clinical case demonstrates a successful outcome of the surgical treatment of pseudarthrosis of vertebral body (mobile nonunion vertebral body) in which expandable intravertebral stents allow to perform an internal replacement of the necrotic vertebral body by creating intrasomatic cavities and filling them with bone graft, obtaining a totally bony vertebra with a metallic endoskeleton, which is biomechanically and physiologically more similar to the original one. This biological internal replacement of the necrotic vertebral body technique can be a safe and effective alternative over cementoplasty procedures or total vertebral body corpectomy and replacement for vertebral pseudarthrosis and may have several advantages over them, however long-term prospective studies are needed in order to prove the effectiveness and advantages of this surgical option in this rare and difficult pathological entity.